The study of antimicrobial, anti-cancer, anti-inflammatory and α-glucosidase inhibitory activities of Nigronapthaphenyl, isolated from an extract of Nigrospora sphaerica - Kushan M. Ukwatta; Jennifer L. Lawrence; C. D. Wijayarathna (Mycology, 2019)
A new compound, nigronapthaphenyl, was extracted from the endophytic fungus Nigrospora sphaerica isolated from a mangrove plant Bruguiera gymnorrhyza. The structure of the compound was elucidated by analysis of 1D and 2D NMR spectra and mass spectrometric data. It was tested in vitro for its antimicrobial activity, cytotoxicity, anti-inflammatory activity and for its ability to inhibit α-glucosidase. Nigronapthaphenyl showed antibacterial activities against Bacillus subtilis TISTR 088 and Bacillus cereus TISTR 688 with MIC values of 4 and 2 μg/mL respectively. Cytotoxicity against colon cancer cell line HCT 116 was found to be an IC50 value of 9.62 ± 0.5 μM . This further showed potential anti-inflammatory activity amounting to an IC50 of 6.2 ± 0.5 μM and also α-glucosidase inhibitory activity, with an IC50 value of 6.9 ± 0.5 μM.